Coupling Coordination Degree Measurement and Forecast of Poverty Alleviation, Energy Conservation, and Ecological Protection: Evidence from 30 Provinces and Cities in China - Shuai Guan; Qichun Zhang (Discrete Dynamics in Nature and Society)
As China experiences rapid economic development, tasks involving poverty alleviation, energy conservation and ecological protection need to be addressed. Whether poverty alleviation, energy conservation and ecological protection in China have coordinated development has become a question worth studying. Based on the coupling coordination degree model and the GM (1, 1) model, this paper calculates and forecasts the development level of poverty alleviation, energy conservation and ecological protection of 30 provinces (cities) in China and analyses the synergy of the three systems spatially and temporally. The results show that first, from 2010 to 2019, the development level of China’s poverty alleviation system, energy conservation system and ecological protection system presented increasing trends, but regional differences could be seen in development trends. Second, the coupling coordination degree of the three systems in China showed an upwards trend. The average coupling coordination degree of 30 provinces (cities) rose from slight coordination in 2010 to moderate coordination in 2019. Third, in the following years, development level will still be on an upwards trend in the four regions of China from 2020 to 2025. The development level of the ecological protection system will be the highest in China, and poverty alleviation and energy conservation will rank second and third. Fourth, the coupling coordination degree of the three systems of 30 provinces (cities) in China will rise significantly, indicating that the development of the three systems in China will be more coordinated in the following years.